Evaluating the Effectiveness of Amarantha and Chlorhexidine Mouthwashes in Chronic Generalized Gingivitis: A Randomized Clinical Trial - Swapna Ediga; Ruchi Gulati; Heeralal Chokotiya; Meet Modi; Vasundhra Sethi; Sagar Kumar Kashyap (Journal of Pharmacy and Bioallied Sciences)
Aim: The current study’s objective was to assess and contrast the benefits of herbal and chemical mouthwash in patients with persistent, widespread gingivitis. Material and Method: Forty-five patients between the ages of 30 and 50 having persistent generalized gingivitis were enrolled in the study and randomly assigned to three groups: Group A received oral prophylaxis, group B received oral prophylaxis and prescribed chemical mouthwash, group C received oral prophylaxis and prescribed herbal mouthwash. The patients were under observation for forty-five days. At the baseline, 7th, 30th, and 45th day gingival index was measured, and the data were statistically analyzed. The one-way ANOVA and Tukey’s post-hoc test were performed. Result: The gingival index showed a significant difference. Over time, the gingival index tends to decrease with the use of herbal mouthwash. Conclusion: In summary, our initial investigation demonstrates that herbal mouthwashes are just as successful in reducing gingival inflammation as chlorhexidine further significant difference observed in 30th and 45th day with chlorhexidine. Therefore, in addition to routine dental care, these ayurvedic medications can be taken to reduce gingivitis.